A bonded particle model for analysis of the flaw orientation effect on crack propagation mechanism in brittle materials under compression - Manouchehrian, A.; Sharifzadeh, Mostafa; Marji, M.; Gholamnejad, J. (Elsevier, 2014)
In this paper, implementation of a bonded particle model (BPM) using PFC2D was proposed to study the effect of the flaw orientation on the crack propagation mechanism in brittle materials such as rocks under various compressive loads. For this purpose, several pre-cracked rock specimens with different orientation of flaw under uniaxial and biaxial loads were modeled in PFC2D (bonded particle model) and crack propagation processes were monitored. According to the results, by varying the flaw inclination angle (β), two types of the secondary crack propagation mechanism were detected. Also, it was concluded that the confinement stress affected the crack initiation and propagation mechanism and the increase of it made the crack initiation angle steeper.